Green and lean sustainable development path in China: Guanxi, practices and performance - Zhan, Yuanzhu; Tan, Kim Hua; Ji, Guojun; Chung, Leanne; Chiu, Anthony (Elsevier, 2018)
Globalisation has created both drivers and pressure for Chinese organisations to enhance their business performance as well as environmental performance. Green and lean practice is emerging as a critical approach for Chinese organisations to achieve sustainable development and improve organisational performance. By conducting empirical studies from 172 respondents on green and lean practice in different Chinese organisations, this research shows how green and lean practice affects organisational performance and how this association is affected by guanxi. The findings explain that guanxi between organisational partners improves the positive effect of green and lean practice on organisational performance. The results of this paper offer helpful insights into how managers should enhance their guanxi initiatives, in order to improve environmental and business performance over their supply chains. The paper also suggests the limitations of this research, as well as directions for future research.